Research on the relationship between viscoelasticity and shock isolation performance of warp knitted spacer fabrics - Jin JIANG (Journal of Hebei University of Science and Technology, 2016)
Warp-knitted spacer fabric which is commonly used in impact protection is selected as test materials to study the relationship between viscoelasticity and the performance of shock isolation. A damping test platform is built to test different specifications of warp-knitted spacer fabric including compression elastic modulus, damping ratio and the residual impact load under different impact speed. Experimental results show that there is no clear correlation between the shock isolation performance and the viscidity or the elasticity. Accordingly, viscosity-to-elasticity ratio is proposed to characterize the relationship between viscoelasticity and shock isolation performance, and it is found that appropriate viscosity-to-elasticity ratio within a certain range can help to achieve better shock isolation performance.